ASAL USUL PANGERAN MENANG JAGAD DAN RATU MINAK KEMALA DI KAMPUNG NEGARA BATIN, KABUPATEN WAY KANAN - Prasetyo, Nereus Eko; Sahmega, Bagus; Prayogi, Rahmat (STKIP Pesisir Selatan, 2025)
This research is about the origin of Pangeran Menang Jagad and Minak Kemala in Kampung Tua, Negara Batin District, Way Kanan Regency. The formulation of the problem of